Pengaruh Penerimaan Dana ZISWAF, ROA, Dan Laba/Rugi Bersih Tahun Berlangsung Terhadap Pendapatan Mudharabah Dengan Firm Size Sebagai Variabel Moderasi Pada Perbankan Syariah Tahun 2015–2023 - Izzudin, Dani; Budianto, Eka Wahyu Hestya (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to analyze the effect of receiving ZISWAF funds, return on assets (ROA), and net profit/loss on Mudharabah income with company size as a moderating variable in the period from 2018 quarter 1 to 2023 quarter 3. The data used in this research comes from companies listed on the Indonesian Stock Exchange (BEI). The sampling method used was purposive sampling, with a total sample of 5 banks over a six-year period. Data analysis was carried out using panel data regression analysis and moderated regression analysis (MRA) using Eviews 12 software. The results of the research show that ZISWAF fund receipts, return on assets (ROA), and net profit/loss have a significant influence on the company's Mudharabah income. In addition, company size moderates the relationship between these variables and Mudharabah income. This research contributes to the understanding of the factors that influence company financial performance, especially in the context of ZISWAF fund receipts, return on assets (ROA), and net profit/loss.